Calculator search results

Formula
Graph
$y = 3 x ^ { 2 } - 6 x + 2$
$y = 0$
$x$Intercept
$\left ( 1 - \dfrac { \sqrt{ 3 } } { 3 } , 0 \right )$, $\left ( \dfrac { \sqrt{ 3 } } { 3 } + 1 , 0 \right )$
$y$Intercept
$\left ( 0 , 2 \right )$
Minimum
$\left ( 1 , - 1 \right )$
Standard form
$y = 3 \left ( x - 1 \right ) ^ { 2 } - 1$
$$3 x ^ { 2 } - 6 x + 2 = 0$$
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo